UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS (TGT) PADA SISWA KELAS XII.IPA 3 SMAN 1 TALAMAU - Indrayerli, Indrayerli (Jurnal Manajemen Pendidikan, 2017)
Based on student learning outcomes Class XII.IPA 3 SMAN 1 Kinali in subjects Sub mathematics Using the transformation of geometry that can be stated in the matrix in solving the problem found that the results of student learning in Mathematics subjects is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in sub Mathematics subjects Using geometric transformations that can be stated in the matrix in problem solving through Teams Game Tournaments (TGT) Learning Model in Class XII.IPA 3 SMAN 1 Talamau District Western Pasaman. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 26 students of Class XII.IPA 3 SMAN 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been proposed, it can be concluded that Teams Game Tournaments (TGT) Learning Model can improve student learning outcomes in sub Mathematics subjects Using geometric transformations that can be stated in the matrix in solving problems in SMAN 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 61.81 (Enough) increased to 83.85 (good) with an increase of 22.04%.